Virtual banking : a guide to innovation and partnering - Schatt, Dan. (New Jersy : Wiley, 2014)
"Technology is permanently transforming the banking industry, and digital payments are the keyElectronic Payments, Mobile Commerce, and Virtual Banking: A Guide to Innovation, Partnering, and Regulation takes a hands-on approach to competing in the modern banking environment. Former PayPal Head of Financial Innovation Dan Schatt explores the reasons behind the massive consumer migration away from traditional banks, and provides clear, actionable guidance on beating new banking models at their own game. Digital payment is the hottest topic in banking today, and is set to define the future of the industry.Consumers are rapidly abandoning traditional banks in favor of institutions that are lower-cost and more consumer-centric. Between the pace of financial regulatory reform and the cloud computing revolution, the old banking model is on the fast track to extinction. Electronic Payments, Mobile Commerce, and Virtual Banking provides the information banks need to compete in this new environment, and details the integral implementation actions that will allow them to thrive. The book discusses real-world innovations from banks, non-banks, and up and comers, and the heavy competition from the new outsource bank model. Topics include: The changing POS landscape and the need for digital wallet partnerships Shifting gears to greenfield market opportunities versus non-profitable markets Digital channel best practices for superior customer experience When to outsource, and what capabilities to truly own Case studies including PayPal, Google, Square, Facebook, Twitter, and more illustrate acceleration of innovation through banking partnerships, as well as the mechanics behind banking's biggest, scariest threats. The trick to surviving the paradigm shift is to embody innovation while providing a superior customer proposition. Electronic Payments, Mobile Commerce, and Virtual Banking: A Guide to Innovation, Partnering, and Regulation provides the inside track on managing the shift and dominating the new marketplace"--
Machine generated contents note: Foreword Preface Acknowledgments Introduction: Innovating Through Scarcity The Influence of Cloud on Innovation The Influence of Smartphones Big Data = Big Driver of Innovation Taking a Cue from Retailing The Enemy of My Enemy Is My Friend Reconciling Innovation and Regulation In Search of New Payments Revenue Streams New Skillsets for a New Era A Roadmap for This Book Notes Chapter 1: Consumer Empowerment Knocking At the Door How Mobile is Reshaping Consumer Expectations in Financial and Retail How Mobile is Changing Consumer Behavior Mobile is Blurring the Lines between Digital and Physical The Uber-ization of Mobile 'Top of Wallet' to "Top of Mobile" The QR Code What Banks Can Learn From Starbucks Leveling the Playing Field With LevelUp From Mobile Banking to Tablet Banking Mobile Models for the Emerging Markets What's Next? More of the Same Notes Chapter 2: Social and Financial Services Maintaining Relationships and Relevance through Social strategies Digital, Data, and the Future of Banking Social Media Experiences in Banking Gamification Personal Financial Relationship Mapping Capitalizing on Social Banking Moven: Delivering Banking through Social Context Social Banking in Europe and Asia Social Login, Sharing, and Top of Wallet Peer to Peer Lending: Blending Social and Banking Beyond the Hype: Partnering For The Future with Peer-to-Peer Lenders Lending Club: A Win-Win for Banks and Their Customers An Investor's Perspective on Social Banking and the Emergence of Bitcoin Message To Banks: Be a Smaller Part of a Bigger Pie Notes Chapter 3: Connected Financial Commerce Location-based Services, Mobile Commerce, and Digital Wallets The "Local" Digital Wallet The New Retail Experience Retail 2.0 and Its Effect on Payments Entrepreneurs, Developers, and Financial Services I d Context Banking: The Next Step Low Energy Bluetooth, Hardware, and the Future of Commerce iBeacon and EasyPay: The Future of In-store Payments? PayPal's iBeacon: Proximity and Context Google Glass for Finances In Search of the Digital Wallet The Who's Who of Digital Wallets What's Next? Notes Chapter 4: Innovating with Big Data and Open Platforms Competing in a World of Unlimited Data and Storage The Rise of Platform Services Application and Programming Interfaces (APIs) for Online and Mobile Commerce Coping Strategies for Banks PayPal's Bold Bet: Unleashing Innovation Through an Open Platform App Stores For Banks: Will It Work? What's Next? Notes Chapter 5: The Smart Pipe Models that Will Survive the Next Generation The Prepaid Model Prepaid Nation: Redefining What A Bank Can Be2 The 'Underbanked' and Opportunities for Innovation MoneyGram: An Example of Innovation Through Partnering Innovative Ways To Expand Access- PayNearMe How Innovative Banks Are Partnering For Innovation The CEO, CIO Relationship Driving the Innovation of ING DIRECT Canada6 A Whole New Era7 A Venture Capitalist's Look at The Future of Banking Technology As An Enabler And Partner... What the Next 50 Years Might Hold? The Future Bank Bundle: Platform-Relationship-Utility Notes Chapter 6: Math Based Currencies How Bitcoin May Prove Transformational to The Financial Services Industry ( George Peabody) Entering The Age of Context Intro to Math-based Currencies Why "Math-based Currencies"? History of Digital Currencies Math-based Currency Characteristics Bitcoin: The First MBC Is it Bitcoin, Bitcoin, or Just BTC How Bitcoin Works Counterfeiting No More Completing the Bitcoin Ecosystem Bitcoin Use Cases in Payments Improving the Bitcoin Protocol Ripple: The Second MBC International Remittance Rails Interbank Settlement Building Trust with MBCs Automating Transaction Policies Moving Ahead with MBCs Conclusion About the Companion Website About the Author Index .
Includes index.
Keywords: Banks and banking; Electronic funds transfers; BUSINESS & ECONOMICS / Banks & Banking